(untitled) (The Pakistan Development Review, 1975)
The operations of multinational corporations (MNCs)1 have recently been the subject of much discussion as well as controversy internationally. The issues involved have centred around the advantages and gains, as opposed to the costs, accruing to the capital exporting countries, or the host countries or the MNCs. However, the debate has acquired nationalist and, for this reason, emotional undertones. This is not surprising. The past activities of a number of MNCs are tainted with colonial exploitation or its near equivalent. Anaconda Copper and Chile, United Fruit and the Banana Republics, Union Minere and Congo, Firestone and Liberia; and, more recently, the "seven oil majors" and the Middle East countries have been in the news again.2 These and similar cases display a common factor. They relate to the exploita¬tion by the MNCs of either mineral or agricultural resources of the Third World countries. Our earlier experience with the East India Company is now history, of course. More recently the country’s limited mineral wealth, as well as the non-plantation nature of its agricultural sector, has kept Pakistan outside the..................